Karya â€œLorongâ€ Sebuah Eksperimentasi Penataan Ruang Pentas - Saryuni Padminingsih (Greget, 2010)
In its beginning, Indonesian dance was born out of a variety of spaces, ranging from communal areas to one occupied by royalty. Communal spaces as according to Ashadi Siregar (1991) forms an integral and import part of the basic conventions of communicative art. In the context of Javanese areas itself. Unmistakenly, the highly populated Kemlayan village is made accessible through narrow roads called lorong, The narrow lorong(s) of Kemlayan then forms the basis of a new dance choreography. Placed in an open area, the work begins with the belief that spatial settings should be able to stand on its own as a piece of visual art. Due to this nature, the work seeks to manifest itself as an alternative work in the global development of dance.The concept is approached through observational means as well as through direct involvement with the environment in order to have a phenomenal experience of the society.On the same page, the spatial setting is approached through various theoretical and practical studies to the point of the actualization of the project.In tandem with such a notion, bodily movements are explored through various movement experiments and exploration that are backed by a sense of aesthetics developed through theoretical approaches and temporal experiences.The work’s development undergoes a process that involves imagination, interpretation, and creativity which can be further understood through : 1. The soul of the work is engendered through the choreographer’s experience with the complexity, grind, guts, and gumption of life as well as the problems that affects one’s inner being, 2. The form of the work takes upon the tugs of visual aesthetics that is experienced on a daily basis by viewers such as the acts of sitting, walking, jumping, climbing, shivering and many others. Along with such a notion, the music is built unto each dancer’s everyday auditory experiences such as talking and shouting as well as media derived sounds such as the radio or bamboo being struck. Staged on an open plane, the spatial setting is composed of narrow lorong(s) made of bamboo, glass, and pellucid plastic arranged in such a manner that it can be seen through from various viewpoints. The artistic lighting concept then summarizes the presence of visual aesthetics and displays a myriad of effects through 7 different performances, namely, Lorong Kemlayan, Lorong Anyaman, Lorong Kerumunan, Lorong Transparan, Lorong Lumpur, Lorong Jalan Setapak, Lorong Gelap.Keywords: Lorong, passage, experimental, form, Kemlayan